Determining how different ventilation shutdown plus methods change the electroencephalography, blood chemistry, corticosterone, and heat shock protein 70 of laying hens - Harding, Kari L.; Boot, Emmillie; Evans, Jackson O.; Shah, Sanjay B.; Malheiros, Ramon D.; Anderson, Kenneth E. (Frontiers in Physiology, 2025)
The poultry industry faces a major impediment in dealing with highly pathogenic avian influenza (HPAI). Large outbreaks have resulted in depletion of available resources needed for desired depopulation methods, leading to the need for alternative methods. This study was conducted to explore alternative ventilation shutdown procedures and how they affect laying hens throughout the process. Three treatments evaluated were ventilation shutdown plus heat (VSDH), ventilation shutdown plus heat and relative humidity (VSDHRh), and ventilation shutdown plus carbon dioxide (VSDCO2). There were two phases used: one phase was used to study treatment effects on the hens’ EEG responses from beginning to time of death and how laying hens behaved. Phase 2 examined how these treatments affected hen blood chemistry and HSP70 during the process. VSDCO2 had a significantly quicker time of death (P = 0.0003), and VSDH and VSDHRh were not different. There were no differences in pre- or post-corticosterone levels in Phase 1; however, there was a trend (P = 0.07) toward significance in the post corticosterone levels. Heat shock protein 70 (HSP70) levels were higher (P = 0.0001) in the VSDCO2 treatment, which could be due to the protein upregulation to prevent apoptosis. In Phase 2, VSDH corticosterone had a significantly greater treatment effect compared to VSDHRh and VSDCO2. corticosterone levels were significantly greater than those of VSDHRh. There were no significant treatment effects in Phase 2 for HSP70 expression; however, the sequence was significant, with the HSP70 being significantly greater at 75% to the average time of death than at 100% to the average time of death. Overall, VSDHRh could be a good alternative for the industry to use to rapidly depopulate laying hen facilities. However, more research on this treatment and more in-depth stress parameters measured needs to be conducted to fully determine how it affects laying hens.